Making Literature Matter: An Anthology for Readers and Writers - Schilb, John and Clifford, John. (Boston Bedford/St. Martins, 2003)
The mission of this anthology is to combine an exceptionally diverse selection of literary works with unusually thorough writing instruction that helps students read and write about literature thoughtfully.
Keywords: Literature